PENGARUH FAKTOR LINGKUNGAN IBU DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH PESISIR - Susilawati Susilawati; Meilisa Luthfiah (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Background: Environmental factors and maternal personal hygiene are related to the incidence of diarrhea. One of them is the presence of vectors caused by poor sanitation and SPAL and CTPS. Purpose: This literature review aims to determine the relationship between environmental factors and maternal personal hygiene with the incidence of diarrhea. Method: The method used in writing a literature review is a traditional literature review. Data sources come from Google Scholar and the Garuda portal in the 2015-2020 period. The keywords used are "diarrhea incidence, environmental factors and maternal personal hygiene". After screening, there were 22 reference articles. Results: The results showed that there were 18 out of 22 journals which concluded that environmental factors were one of the causes of diarrhea, 13 of 22 journals concluded that maternal personal hygiene was one of the causes of diarrhea. The dominant maternal environmental and personal hygiene factors trigger the incidence of diarrhea, namely sanitation, SPAL and CTPS. Bad CTPS is more dominant in causing diarrhea with an OR value of 6.985. Conclusion: Conclusion of this literature review is that the causes of diarrhea in toddlers are more dominated by sanitation conditions, SPAL and one of the mothers' personal hygiene, namely poor CTPS. Good CTPS is using soap and running water when washing hands. Therefore, improving sanitation, SPAL and good application of CTPS is one way to minimize the incidence of diarrhea